Frequent food insecurity among injection drug users: correlates and concerns - Strike Carol; Rudzinski Katherine; Patterson Jessica; Millson Margaret (BMC, 2012)
Abstract Background Food insecurity and nutrition are two topics that are under-researched among injection drug users (IDUs). Our study examined the extent and correlates of food insecurity among a sample of IDUs and explored whether there is an association between food insecurity and injection-related HIV risk. Methods A cross-sectional survey was conducted using interviewer-administered questionnaires. Data were collected at a needle exchange program in London, Ontario, Canada between September 2006 and January 2007. Participants included 144 English-speaking IDUs who had injected drugs in the past 30 days. Participants were asked about their socio-demographic characteristics, HIV risk behaviours, food insecurity, and health/social service use. Results In the past 6 months, 54.5% of participants reported that on a daily/weekly basis they did not have enough to eat because of a lack of money, while 22.1% reported this type of food insecurity on a monthly basis. Moreover, 60.4% and 24.3% reported that they did not eat the quality or quantity of food they wanted on a daily/weekly or a monthly basis, respectively. Participants reported re-using someone else's injection equipment: 21% re-used a needle, 19% re-used water, and 37.3% re-used a cooker. The odds of sharing injection equipment were increased for food insecure individuals. Conclusions Findings show that IDUs have frequent and variable experiences of food insecurity and these experiences are strongly correlated with sharing of injection-related equipment. Such behaviours may increase the likelihood of HIV and HCV transmission in this population. Addressing food-related needs among IDUs is urgently needed.